KNOWLEDGE AND AWARENESS ON HIV/AIDS OF SENIOR HIGH SCHOOL STUDENTS TOWARDS AN ENHANCED REPRODUCTIVE HEALTH EDUCATION PROGRAM - Jesus, A O; Martinez, Ma. Cecilia O (LIFE: International Journal of Health and Life-Sciences, 2019)
The study determined the levels of knowledge and awareness on HIV/AIDS of 369 senior high school students of Los Banos Laguna, Philippines, towards an Enhanced Reproductive Health Education Program using an adopted and modified questionnaire from the research study of Marc Lester Quintana in 2018. The results were: high level of knowledge on HIV/AIDS in terms of transmission, prevention and protection; high level of awareness about the effects of HIV/AIDS in terms of physical, psychological, socio-economic and spiritual; there is a significant relationship between the levels of knowledge and awareness about the effects of HIV/AIDS. It was recommended that: senior high school students to become more knowledgeable and updated about HIV/AIDS; they should participate in activities in school in partnership with their educators and school administrators for the implementation of the Enhanced Reproductive Health Program, as permitted by their parents; and lastly future researchers to use this study and its output as a reference for similar future endeavors.